COMPARATIVE ANALYSIS OF COLOR IDIOMS IN ENGLISH AND KARAKALPAK LANGUAGES - Aymanova, Sh. (SCIENCE and SOCIETY, 2023)
This article is focused on the typology of colors and universal color (black) terms proposed by Berlin and Kay (1969), which is currently being studied, and the paper analyzed colors. The research data was sourced from dictionaries of idiomatic expressions, the Collins COBUILD Dictionary of Idioms, Oxford Idioms Dictionary for Learner's of English, and actuality of phraseological units in Karakalpak language for Karakalpak color idioms. In the article, the views of the authors who actively contribute to the creation of phraseology of the English and Karakalpak languages were analyzed.